AN OBSERVATIONAL STUDY ON THE ROLE OF DECAF SCORE IN PREDICTING PROGNOSIS IN PATIENTS WITH ACUTE EXACERBATION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE. - Sharma, Suresh; Nath, Neena; Ahmed, Abdul Barik; Chanda, Rituporna; Choudhury, Manas; Dhar, Sourav (Student’s Journal of Health Research Africa, 2023)
Objective: The study was done to validate the DECAF score for the prediction of prognosis in AECOPD patients. Methodology: 92 AECOPD patients were given scores as per the DECAF system. Patients were monitored during their whole hospital stay. The final results were classified as death and recovery. DECAF score’s importance for the prediction of clinical outcomes was analyzed. Result: Out of 92 patients evaluated, 27 had a DECAF score range between 0-1 (low risks), 5-9 had a DECAF score range between 2-4 (intermediate risks), and 6 had a DECAF score range between 5-6 (high risks). The high-risk group experienced a 100% fatality rate. On the other hand, there was no mortality seen in patients with DECAF scores 0-4 & all the patients recovered successfully. Conclusion: DECAF score uses routine parameters to classify AECOPD Patients into clinically relevant risk groups. Doctors are benefitted from this regarding management purposes.